Means of Representation of the Author’s “I” in the Media Text - V. Ivanova, Maria; S. Papusha, Irina; V. Ledeneva, Valentina (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this article is to describe the actual means of representation of one of the anthropocentric phenomena in modern media text—the author’s “I.". The study was carried out on the basis of such methods as general scientific methods of observation, analysis and description; description of the field of linguistic tension of a complex syntactic whole. The category of the author is regarded as obligatory in the study, while the intentions of the producer of the text are necessary to be fully represented in media text. The complex syntactic whole in the article was considered in the system of means of representation of the author’s "I,” and influence on the addressee (recipient) was recognized as accumulating its most significant semantic components. The following conclusions were drawn: The recipient, through the field of linguistic tension of a complex syntactic whole, recognizes intentional motivations of the author of the media text, directly related to the linguistic side of the organization of communicative units, which allows us to reflect and to perceive the features of the author’s “I” as a system of worldview, values, and beliefs due to the specifics of the mental and linguistic complex of the linguistic personality.